Perilaku Konsumen Dalam Pengambilan Keputusan Pembelian Pada Nineteeone Coffee Salatiga - Bayu Aji Susilo; Ricky Arnold Nggili (Lembaga Pengembangan Kinerja Dosen, 2025)
This study focuses on the analysis of consumer behavior in making coffee purchasing decisions at Mitra Nineteeone Coffee located in Salatiga, especially on Jalan Adi Sucipto. This study does not cover consumer behavior at other coffee shop partners in Salatiga. This study uses a qualitative method to deeply understand the experience and behavior of consumers in making coffee purchasing decisions, especially at Nineteeone Coffee Salatiga. This study was conducted at three Mitra Nineteeone Coffee, Salatiga City, Central Java, located around Jalan Adi Sucipto, Jalan Kartini, and Jalan Diponegoro. This study does not cover other branches or coffee shops that have similar concepts. To obtain accurate and in-depth data, this study applies several data collection techniques, namely interviews and observations. The results of the study are that purchasing decisions are greatly influenced by individual perceptions, motivations, and attitudes, especially when consumers have emotional or personal involvement with a product or brand.